Effect of Prenatal Hypoxia in Transgenic Mouse Models of Preeclampsia and Fetal Growth Restriction. (April 2014) - Rueda-Clausen, C. F.; Stanley, J. L.; Thambiraj, D. F.; Poudel, R.; Davidge, S. T.; Baker, P. N.
Mice lacking endothelial nitric oxide synthase (eNOS − /− ) or catechol-O-methyl transferase (COMT −/− ) exhibit a preeclampsia-like phenotype and fetal growth restriction. We hypothesized that a hypoxic insult would result in a more severe phenotype. Pregnant eNOS −/−, COMT −/− and control (C57BL/6J) mice were randomized to hypoxic (10.5% O2 ) or normal conditions (20.9% O2 ) from gestational day 10.5 to 18.5. Hypoxia increased the blood pressure in all genotypes and proteinuria in C57BL/6J and eNOS −/− mice. Fetal survival was significantly reduced following hypoxia, particularly in eNOS −/− mice. Birth weight was decreased in both C57BL/6J and COMT −/− mice. Placentas from COMT −/− mice demonstrated increased peroxynitrite. Despite similar hypoxia-induced effects on maternal blood pressure and proteinuria, eNOS −/− embryos have a decreased tolerance to hypoxia. Compared to C57BL/6J, COMT −/− mice exhibited less severe changes in proteinuria and fetal growth when exposed to prenatal hypoxia. This relative resistance to prenatal hypoxia was associated with a significant increase in placental levels of peroxynitrite.